Disruption of component processes of spatial working memory by electroconvulsive shock but not magnetic seizure therapy - McClintock, Shawn M.; DeWind, Nick K.; Husain, Mustafa M.; Rowny, Stefan B.; Spellman, Timothy J.; Terrace, Herbert; Lisanby, Sarah H. (The international journal of neuropsychopharmacology, 2013)
Self-ordered spatial working memory measures provide important information regarding underlying cognitive strategies, such as stereotypy. This strategy is based on repetitive sequential selection of a spatial pattern once a correct sequence has been identified. We previously reported that electroconvulsive shock (ECS) but not magnetic seizure therapy (MST) impaired performance on a spatial working memory task in a preclinical model. Here we tested the hypothesis that ECS disrupted stereotyped patterns in the selection of spatial stimuli. In a within-subject study design, we assessed the effects of ECS, MST, and sham on stereotypy and reaction time in a preclinical model. Stereotypy was assessed by the correlation of actual and predicted response patterns of spatial stimuli. Predicted patterns were based on performance during baseline sessions. ECS resulted in lower correlations between predicted and actual responses to spatial stimuli in two of the three subjects, and it also disrupted stereotypy. For one subject, there was change in the predictability of the spatial locus of responses between experimental conditions. For all three subjects, reaction time was significantly longer in ECS, relative to MST and sham. This is the first study to examine the effect of ECS, and to contrast the effects of ECS and MST, on spatial working memory component processes. Our preliminary findings show that ECS, but not MST decreased stereotypy and increased reaction time. This line of investigation may have significant implications in our understanding cognitive component processes of memory function and impairment.